Relationship between Online Academic Self-Efficacy and Procrastination Behavior in Students - Tuwo, Praysi Theresia; Wibowo, Doddy Hendro (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Covid-19 pandemic has an effect on students which requires them to do online learning. This condition has an impact on students to carry out procrastination behavior. This study aims to determine the relationship between online academic self-efficacy and procrastination behavior in students. The research method used is quantitative with a correlational design. With a sample of 266 participants who are actively studying in Salatiga, and use techniquescluster random sampling Data collection usingonline academic self-efficacy scale, and procrastination scale. The research results show that the valueRxy = -0.097 and sig.= 0.114 which meansthere is a negative relationship betweenself-efficacyonline academic and procrastination behavior in students.